District-level strategies to control the HIV epidemic in Zimbabwe: a practical example of precision public health - Richard Makurumidze (BMC Research Notes, 2020)
Abstract Objective We conducted a descriptive cross-sectional study using survey and programme data to assess district-level performance along the HIV care cascade (HIV testing target achievement, linkage to ART and ART coverage) in order to formulate district-specific recommendations, taking into consideration prevalence and yield of testing. Results Data from 60 districts were analysed. Forty-eight districts (80.0%) surpassed 90% of their 2018 HIV testing targets. Linkage to ART was less than 90% in 40 districts (83.3%). Thirty districts (50.0%) had ART coverage above 90%. Of the 30 districts with suboptimal (< 90%) ART coverage, 18 districts had achieved high HIV testing target but with suboptimal linkage to ART, 6 had achieved high HIV testing targets and high linkage to ART, 4 had both suboptimal HIV testing target achievement and linkage to ART and 2 had suboptimal HIV testing target achievement and high linkage to ART. Priority should be given to districts with suboptimal ART coverage. Remediation strategies should be tailored to address the poorly performing stage of the cascade in each of the districts.